2016
DOI: 10.1016/j.biomaterials.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic culture improves cell reprogramming efficiency

Abstract: Cell reprogramming to pluripotency is an inefficient process and various approaches have been devised to improve the yield of induced pluripotent stem cells. However, the effect of biophysical factors on cell reprogramming is not well understood. Here we showed that, for the first time, dynamic culture with orbital shaking significantly improved the reprogramming efficiency in adherent cells. Manipulating the viscosity of the culture medium suggested that the improved efficiency is mainly attributed to convect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, we found that reprogramming efficiency decreased when the total vector concentration was too high. Previous studies have shown that cell density is critical for reprogramming (Zhao et al 2015 ; Sia et al 2016 ). Thus, to optimize cell density, we plated BJ cells transfected with 9 µg episomal vectors onto Matrigel coated 6-well dishes at a density ranging from 1.0 × 10 4 to 3.0 × 10 5 cells per well.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that reprogramming efficiency decreased when the total vector concentration was too high. Previous studies have shown that cell density is critical for reprogramming (Zhao et al 2015 ; Sia et al 2016 ). Thus, to optimize cell density, we plated BJ cells transfected with 9 µg episomal vectors onto Matrigel coated 6-well dishes at a density ranging from 1.0 × 10 4 to 3.0 × 10 5 cells per well.…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming was more rapid and more efficient in the engineered hydrogels when compared with traditional 2D culture (167). Nutrient transport within cultures has also been demonstrated to play a significant role in reprogramming efficiency (168).…”
Section: Improving Reproducibilitymentioning
confidence: 98%
“…In fact, Sia et al . conversely reported enhancement in the reprogramming efficiency of mouse iPSC with dynamic culture applied at mid to late phase of reprogramming [31]. The authors attribute this to convective mixing that prevents cell cycle arrest as cells reached confluency.…”
Section: Biomaterials In Ipsc Reprogrammingmentioning
confidence: 99%